Development of based learning media with App Inventor - Satria, Erwinsyah; Musthan, Zulkifli; Cakranegara, Pandu Adi; Arifin, ardian; Zulvia Trinova (Politeknik Ganesha Medan, 2022)
The research aims to develop an Android-based learning media. The stages of the research are analysis, implementation, and evaluation. The participants of the research were students at West Kalimantan Vocational High School. The research method used is Research and Development with the ADDIE approach. Data analysis used descriptive qualitative. The subjects in this study were students of class X AK 1 and X AK 2 at Vocational High School West Kalimantan, totaling 56 students, for a small-scale trial taken 5 students from X AK 1 and 5 students from X AK 2. Research instrument was using a questionnaire with a scale. Research results based on research statements and the development of Android-based learning media with App Inventor on word processing software, it can be concluded that to make applications with App Inventor software it is not enough to just use a browser application. the development of learning media using the App Inventor media after validation with two media experts is very feasible to use and by using this application the teaching and learning process run very independently and make it easier for students to understand the learning material